Physics of superheavy dark matter in supergravity; International Journal of Modern Physics D; Vol. 27, iss. 6 - Addazi A. Andrea; Marciano A. Antonino; Ketov S. V. Sergey Vladimirovich; Khlopov M. Yu. Maksim Yurjevich (2018, 2018)
Title screen